2023
DOI: 10.1002/cam4.5639
|View full text |Cite
|
Sign up to set email alerts
|

Clinical sequencing identifies potential actionable alterations in a high rate of urachal and primary bladder adenocarcinomas

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
(141 reference statements)
0
7
0
Order By: Relevance
“…PBAC shows a lower tumor mutational burden compared with UC, with intact mismatch repair-protein expression and lack of programmed cell death ligand 1 expression in most cases 14,24–26 . However, current studies detected potentially targetable molecular alterations in PBAC in 33.5% to 67% of cases 26,27 . Therefore, molecular testing for predictive biomarkers might be helpful in advanced cases.…”
Section: Urothelial Carcinoma With Glandular Differentiation and Diff...mentioning
confidence: 72%
See 2 more Smart Citations
“…PBAC shows a lower tumor mutational burden compared with UC, with intact mismatch repair-protein expression and lack of programmed cell death ligand 1 expression in most cases 14,24–26 . However, current studies detected potentially targetable molecular alterations in PBAC in 33.5% to 67% of cases 26,27 . Therefore, molecular testing for predictive biomarkers might be helpful in advanced cases.…”
Section: Urothelial Carcinoma With Glandular Differentiation and Diff...mentioning
confidence: 72%
“…14,[24][25][26] However, current studies detected potentially targetable molecular alterations in PBAC in 33.5% to 67% of cases. 26,27 Therefore, molecular testing for predictive biomarkers might be helpful in advanced cases.…”
Section: Primary Adenocarcinoma Of the Urinary Bladder And Potential ...mentioning
confidence: 99%
See 1 more Smart Citation
“… Lee et al (2017) reported EGFR amplification in 23.5% of patients (4/17) by detecting somatic copy number aberrations. More recently, Varadi et al (2023) described EGFR mutations in 9.1% (3/33) of UrC cases by applying next-generation sequencing. These authors detected two samples with amplification and one sample with a missense mutation.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…Notably, in CRC, the most common KRAS mutation is a somatic missense mutation in codon 12 which leads to a single amino acid substitution ( Zhu et al, 2021 ). In this review, we identified a missense mutation in codon 12 ( Sirintrapun et al, 2014 ; Loh et al, 2016b ; Collazo-Lorduy et al, 2016 ; Modos et al, 2016 ; Hang and Pan, 2017 ; Riva et al, 2019 ; Varadi et al, 2023 ) and codon 13 ( Collazo-Lorduy et al, 2016 ; Singh et al, 2016 ; Hang and Pan, 2017 ; Dienstmann et al, 2020 ) in 23% (23/100) and 5% of UrC samples, while KRAS missense mutations in codon 61 ( Modos et al, 2016 ; Riva et al, 2019 ) and codon 146 ( Modos et al, 2016 ) were present in 2% and 2% of cases, respectively. Collectively, these data revealed that the most common mutation of the KRAS gene was the missense mutation in codon 12; this is similar to the KRAS mutational pattern in CRC ( Cha et al, 2016 ).…”
Section: Evidence Synthesismentioning
confidence: 99%